Application of response surface methodology to optimize direct alcohol fuel cell power density for greener energy production. (20th January 2017) - Charoen, Kanin; Prapainainar, Chaiwat; Sureeyatanapas, Panitas; Suwannaphisit, Theeraporn; Wongamornpitak, Kanchaporn; Kongkachuichay, Paisan; Holmes, Stuart M.; Prapainainar, Paweena
Abstract: Energy production from direct alcohol fuel cells depends strongly on the operating conditions. In this paper, the aim was to find the best conditions of direct methanol fuel cells (DMFC) and direct ethanol fuel cells (DEFC) to obtain the maximum power density with the response surface method using Program Design Expert 7.0.0. Three related independent variables, including operating temperature in the range of 30–70 °C, alcohol flow rate in the range of 5–50 ml/min, and alcohol concentration in the range of 0.5–3 M, were covered. Nafion117 was used as an electrolyte and Pt-Ru and Pt were used as catalysts in anode and cathode, respectively. The effect of those variables on the maximum power density was illustrated in the form of quadratic models which predicted the appropriate operating conditions. The Nafion membrane was modified by adding mordenite (MOR) to improve its alcohol permeability. The result from response revealed that the higher operating temperatures and higher alcohol concentrations led to an increase in maximum power density, in both the DMFC and DEFC. The DMFC had a higher maximum power density and greater current than the DEFC had. This was because methanol was easier to oxidize than ethanol In addition, it was found that the MOR content of 1.47 wt% in the Nafion composite membrane reduced the alcohol permeability and resulted in a higher power density. Therefore, the model suggested the optimum conditions to produce greener energy (less resource use with high energy produced). Highlights: Optimum operating condition was predicted using Response Surface Method. Operating temperature and alcohol concentration had great impact on power density. DMFC used composite membrane produced higher power than used pristine Nafion.